Pulmonary Involvement in Children With Systemic Lupus Erythematosus - Dai, Ge; Li, Linlin; Wang, Ting; Jiang, Wujun; Ma, Jie; Yan, Yongdong; Chen, Zhengrong (Frontiers in Pediatrics, 2021)
Background: Symptomatic pulmonary involvement in systemic lupus erythematosus (SLE) seems not uncommon in children. However, there are few data on the characteristics and laboratory parameters of SLE patients with pulmonary involvement. Methods: This was a hospital-based study involving 111 SLE patients from 1 January 2012 to 31 December 2016. The demographic, clinical and laboratory data of the patients were prospectively collected. They were followed as outpatients until December 2019. Clinical characteristics and laboratory parameters of patients with and without pulmonary involvement were compared. Results: Of the 111 patients with SLE, we identified 18 patients (16.2%) with pulmonary involvement. The most common HRCT findings were ground glass opacity, interlobular septal thickening, bilateral diffuse infiltrates, and pleurisy/pleural effusion (55.6%, 50%, 50%, and 44.4%, respectively). SLE patients with pulmonary involvement tended to have a longer disease duration (14 [12-24.5] vs 5 [2-9] months, P<0.01). We also observed a significant association between the presence of anti-Sm antibody, ANCA, Anti-RNP and the presence of pulmonary involvement of SLE (all P < 0.001). Conclusions: Lung involvement was frequent in SLE patients from Southeast China. Patients with a longer duration of symptoms before SLE diagnosis tended to have pulmonary involvement. When children with SLE are found to have anti-RNP antibody and positive ANCA, it should be alert to the occurrence of pulmonary involvement.